Exogenous supplementation of antithrombin III in adult and pediatric patients receiving extracorporeal membrane oxygenation. Issue 5 (May 2020) - Sorial, Mark N; Greene, Rebecca A; Zullo, Andrew R; Berard-Collins, Christine; Willis, Steve
Background: Antithrombin III deficiency can occur with heparin anticoagulation during extracorporeal membrane oxygenation leading to heparin resistance. Antithrombin III supplementation has been shown to improve anticoagulation; however, there is no consensus on appropriate administration. We described the effect of antithrombin III supplementation on coagulation parameters in adult and pediatric extracorporeal membrane oxygenation patients. Methods: We conducted a retrospective cohort study using electronic medical records of patients who received ⩾1 dose of antithrombin III during extracorporeal membrane oxygenation while on continuous heparin. Endpoints included the change in anti-Xa levels and antithrombin III activity at −6 versus 6 h relative to antithrombin III supplementation, and heparin infusion rates at 6 versus 12 h after antithrombin III supplementation. Results: Eighteen patients receiving 36 antithrombin III administrations were analyzed. Mean (standard deviation) anti-Xa values at −6 versus 6 h were 0.15 (0.07) versus 0.24 (0.15) IU/mL ( p -value: 0.250) for pediatrics and 0.19 (0.22) versus 0.31 (0.27) IU/mL ( p -value: 0.052) for adults. Mean (standard deviation) plasma antithrombin III activity at the same intervals were 32% (14.2%) versus 66.8% (25.1%; p -value: 0.062) for pediatrics and 30.3% (14%) versus 52.8% (8.1%; p -value: 0.094) for adults. Mean (standard deviation) heparin rates at 6 versus 12 h after antithrombin III for pediatrics were 23.6 (6) versus 23.5 (6.5) units/kg/h ( p -value: 0.728), and 15.3 (6.6) versus 13.5 (8) units/kg/h ( p -value: 0.188) for adults. Conclusion: Administration of antithrombin III improved anti-Xa levels in both populations, however, did not significantly reduce heparin rates. Our findings suggest that the use of antithrombin III restores heparin responsiveness in patients with low antithrombin III activity and low anti-Xa activity.